2017
DOI: 10.5194/acp-17-4251-2017
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric trace metals measured at a regional background site (Welgegund) in South Africa

Abstract: Abstract. Atmospheric trace metals can cause a variety of health-related and environmental problems. Only a few studies on atmospheric trace metal concentrations have been conducted in South Africa. Therefore the aim of this study was to determine trace metal concentrations in aerosols collected at a regional background site, i.e. Welgegund, South Africa. PM1, PM1–2. 5 and PM2. 5–10 samples were collected for 13 months, and 31 atmospheric trace metal species were detected. Atmospheric iron (Fe) had the highest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…The observed concentrations of most elements were higher than those observed at other regional background regions in Southern Africa and Europe. For elements such as Ca, Al, Fe, and Zn the concentrations in this study were higher than those reported for similar background regions in Welgegung, South Africa (Venter et al, 2017) 3.0 ng/m³), respectively, in comparison to Welgegung (7.9, 6.9 ng/m³) and Puy de Dôme (1.9, 5.8 ng/m 3 ). Sb concentration in this study were higher than at Welgegung and Puy de Dôme sites but lower than those observed at other urban sites (Cheng et al, 2000).…”
contrasting
confidence: 84%
“…The observed concentrations of most elements were higher than those observed at other regional background regions in Southern Africa and Europe. For elements such as Ca, Al, Fe, and Zn the concentrations in this study were higher than those reported for similar background regions in Welgegung, South Africa (Venter et al, 2017) 3.0 ng/m³), respectively, in comparison to Welgegung (7.9, 6.9 ng/m³) and Puy de Dôme (1.9, 5.8 ng/m 3 ). Sb concentration in this study were higher than at Welgegung and Puy de Dôme sites but lower than those observed at other urban sites (Cheng et al, 2000).…”
contrasting
confidence: 84%
“…The results showed that wind speeds in the region are highly influential, by transporting particulate matter from adjoining regions to the sampling location, and thereby, contributing to the TMB, whereas negative correlation with RH is probably due to the wash out processes by rains [87]. Significant correlations (r 2 = 0.41-0.78) of TMB vs AT found in all the localities were attributed to the fact that more favorable atmospheric dispersion conditions and photochemical reactions prevail under warm conditions [88]. Positive correlations of Mn vs Cu (r 2 = 0.83) and Zn (r 2 = 0.76), when p < 0.05 in the rainwater collected at the urban center of Gustavo A. Madero (Table 4), indicated the influence of local road traffic and automobile exhausts [89].…”
Section: Discussionmentioning
confidence: 99%
“…Whiteface Mountain Summit, Beltsville, Ispra, Ryori, and Seokmo-Ri Ga). However, there are other sites in the Northern Hemisphere where a summer maximum is more evident (Vingarzan, 2004), i.e. Joshua Tree and Hohenpeissenberg.…”
Section: Comparison With International Sitesmentioning
confidence: 99%